Tuberculous pyomyositis: a casereport - Leandro Fernandes; Edgard Torres dos Reis Neto; Marcia Aparecida Pozo Pereira; Mirela Carla da Costa Baretta; Adagmar Andriolo (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Female patient, 29 years old, with systemic lupus erythematosus in current use of prednisone and azathioprine, presents with bulging in the forearms, lumbar region and left thigh for 15 days. Ultrasonography and magnetic resonance imaging showed the presence of serous collections in these locations. The material was punctured and the samples were sent to the laboratory. The microbiological examination revealed the presence of acid-resistant bacilli and blood culture in a specific medium was positive for Mycobacterium tuberculosis. Molecular and immunochromatographic tests were positive for M. tuberculosis, and the diagnosis of Tuberculous Piomyositis was closed.